Influência de sistemas pastoris sobre Mahanarva spectabilis (Distant) (Hemíptera: Cercopidae) e o entomopatógeno Metarhizium anisopliae (Metsch.) Sorokin (Hypocreales: Clavicipitaceae) - Matiero, Suellen Chiquito (2015)
Systems Crop-livestock-forest integration are part of the strategies adopted by the Plan ABC- Low Carbon Agriculture, aiming to increase productivity and the economic profitability of the rural population and reduce the risks of environmental degradation, improve the chemical properties, physical and biological soil and connect scientific knowledge to the physiological ecology of plant species and their interactions with the local fauna and flora. Gender sharpshooters Mahanarva (Distant) are part of the complex of insect pests such systems, causing significant damage to pasture component. The feeding habits of this insect causes toxicity in plant tissue, which results in a decrease in forage quality and productivity. Because of this, the objective was to evaluate the effect of pastoral systems Mahanarva spectabilis (Distant) (Hemiptera: Cercopidae) as well as the persistence in soil of entomopathogen Metarhizium anisopliae (Metsch.) Sorokin (Hypocreales: Clavicipitaceae). The evaluations were performed in three treatments, namely: system monoculture Urochloa bryzantha cv Marandu, silvopastoral system of three triple rows of Eucalyptus urograndiscultivation in between rows of U. bryzantha and agrosilvopastoral system, consisting of three triple rows of eucalyptus and soybean cultivation between rows in the first season and maize intercropped with U. bryzantha the second season, remaining the forage after harvest of corn for cattle feed. We evaluated the number of live nymphs of M. spectabilis and nymphs infected by M. anisopliae per m² in the three treatments. There was a bio-insecticide application of the M. anisopliae base at the beginning of the rainy season due to the insect population has reached the 25 nymphs.m² control level in pasture systems in monoculture and silvopastoral. For the evaluation of the permanence of the fungus in the environment were four soil samples, with the first three in the rainy season and the last in the dry season. The agrosilvopastoral system was rated the most sustainable system because there was not the establishment of leafhopper in the pasture, so no need of control. The silvopastoral and monoculture systems differ from each other (p <0.001) with respect to the infestation of M. spectabilis, however, after application of the biopesticide, the population remained below the control level in both treatments. Regarding entomopathogen, the fungus was found in all production systems; however, the monoculture system there was a higher percentage of M. spectabilis nymphs contaminated plus more colony forming units on the ground.